The Philosophia perennis of Hellenistic Christianity: Theological and Ecumenical Implications of Fr. Georges V. Florovsky's View - Toroczkai, Ciprian Iulian (Review of ecumenical studies, Sibiu, 2017)
This article presents the features and meaning of the phrase Christian Hellenism, as it has been elaborated in the thinking of the Russian patrologist Georges V. Florovsky. He has based his thesis, namely that of the radically Christianized or Churchified, New Hellenism on three main points: 1) faith is always asserted in a philosophical system; 2) Semitic thinking is not radically opposed to Hellenism, because Judaism itself in Jesus's time was a Hellenised Judaism; 3) Greek philosophy was the fertile, even providential environment in which Christianity could formulate and express its own experience. The result was a philosophia perennis, something eternal and absolute in the thinking of the Church. As closure of the study we briefly reflect upon the actuality, and the possibilities and limitations which are implied today in the notion of Christian Hellenism. The implications of Florovsky's vision are thus assessed, both in what concerns the relationship between theology and culture, and in what concerns the ecumenical dialogue.